1993
DOI: 10.1289/ehp.93101s653
|View full text |Cite
|
Sign up to set email alerts
|

Kidney cancer and hydrocarbon exposures among petroleum refinery workers.

Abstract: To evaluate the hypothesis of increased kidney cancer risk after exposure to hydrocarbons, especially those present in gasoline, we conducted a case-control study in a cohort of approximately 100,000 male refinery workers from five petroleum companies. A review of18,323 death certificates identified 102 kidney cancer cases, to each of whom four controls were matched by refinery location and decade of birth. Work histories, containing an average of 15.7 job assignments per subject, were found for 98% of the cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…Early nested case-control studies (38,39) among refinery workers and a later industrywide study (43) showed no association between gasoline exposure and renal cancer. Wong et al (44), in a large cohort study of distribution workers, also found no association.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Early nested case-control studies (38,39) among refinery workers and a later industrywide study (43) showed no association between gasoline exposure and renal cancer. Wong et al (44), in a large cohort study of distribution workers, also found no association.…”
Section: Discussionmentioning
confidence: 98%
“…Poole and colleagues (43) reported findings from a nested case-control study of kidney cancer mortality among male petroleum refinery workers from five U.S. companies. Occupational histories were abstracted from employment records for 102 cases and 408 controls.…”
Section: New Findingsmentioning
confidence: 99%
“…For example, excess risks of RCC have been reported among workers exposed to asbestos [Selikoff et al, 1979;Enterline et al, 1987;McCredie and Stewart, 1993], arsenic [Tsuda et al, 1990;Enterline et al, 1995], polycyclic aromatic hydrocarbons (PAH) [Sharpe et al, 1989;Poole et al, 1993;Mellemgaard et al, 1994;Boffetta et al, 1997], gasoline [Siemiatycki et al, 1988;Partanen et al, 1991;Mellemgaard et al, 1994;Lynge et al, 1997], benzidine [Morikawa et al, 1997], solvents [Lynge et al, 1995], formaldehyde [Hansen and Olsen, 1995], and lead [Steenland et al, 1992, Cocco et al, 1997. Workers employed in certain industries also have been found to have elevated risks, including dry cleaning and laundry workers [Katz and Jowett, 1981;Duh and Asal, 1984;McCredie and Stewart, 1993;Lynge et al, 1995], steel workers [Urbaneja Arrue et al, 1995], textile workers and tailors [Auperin et al, 1994], oil refinery workers [Bertazzi et al, 1989;Shallenberger et al, 1992;Poole et al, 1993;Rushton, 1993], gasoline station attendants [McLaughlin et al, 1985], farmers [Forastiere et al, 1993], printers [Paganini-Hill et al, 1980;Sinks et al, 1992], and coke-oven operators [Redmond et al, 1972;McCredie and Stewart, 1993;Mellemgaard et al, 1994]. Most of these occupations suggest that organic sol...…”
Section: Introductionmentioning
confidence: 99%
“…This apparent contradiction might be explained by other factors such as cigarette smoking, which was not sufficiently considered in the analysis (10). Other epidemiological studies published in 1993, which include a cohort of approximately 100,000 male refinery workers (11) A previously unnotified risk of nasal cancer has recently been reported in service station workers in the Nordic countries by Lynge et al (9). The study also reports an increased incidence of pharyngeal, laryngeal, and lung cancers.…”
Section: Human and Epidemiological Studiesmentioning
confidence: 99%